Development and Validation of a Methodology for Quantification of the Soil Erosion through UAS Photogrammetry - Arriola-Valverde, Sergio (2019)
In this paper, the development and validation of a methodology for quantification of hydric erosion in land plots with low vegetal coverage is proposed, through photogrammetry with unmanned aerial systems (UAS). The process consists of the generation of a historical database of digital elevation models (DEM) over a study area from photogrammetric surveys, which is spatially related to on-site ground control points (GCP). This information is used for the creation of DEMs in a “RASTER” format, from which the displaced volumes of soil are estimated over time. These calculations are totalized from a reference level for the quantification of eroded/displaced soil volumes. This article presents a case study, where relevant aspects are discussed in terms of data collection, control point requirements, and data interpretation, reaching a maximum spatial resolution of about 1 cm/pixel.